Iqbal's theory of personality: a contrastive analysis with Freud - Abdul Razak, Mohd Abbas (LAP Lambert Academic Publishing, 2013)
Man being a universe on the micro-level, has been constantly researched upon from the ancient to the modern times using philosophical and scientific approaches. This study explores the developments that have taken place in the areas of human nature and personality in the West and the Islamic World. The crux of this research provides a contrastive analysis of the personality theories showcased to the world by Freud and Iqbal. The analysis of this study indicates that Freud’s views on man and personality are centered around his ideas on the human sexuality. As a result of that, he has provided a concept on man that is both pessimistic and deterministic in nature. To him, man is an intellectual beast who is doomed to fail as he is caught between the warring parties of his psychic components. In contrast, Iqbal has promoted many positive ideas about man and the latent powers of the human psyche. His theory of personality is not only dynamic in nature but also inspires man to sink into his psyche to bring the best out of him. Iqbal believed that by actualizing the good elements of the psyche, man can transform this world into a better place for the benefit of humanity.